THE EFFECTIVENESS OF TABOO GAME TO IMPROVE STUDENTS’ VOCABULARY MASTERY - nila sari, santika dewi; Sri Agung, Winantu Kurnianingtyas (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2023)
This article has purpose to investigate whether there was a significant difference between the vocabulary mastery who were taught by taboo games and who were not of the seventh grade at MTs. Ma’arif Balong, Ponorogo. Quantitative research within experimental design was applied in conducting the research. Experimental class and control class were chosen as research subject. In collecting the data, test and documentation were used. Then, they were analysed using t-test with SPSS 25. The results of this research showed that the mean of post-test in the experimental was 80,19 while the mean of the post-tests in the control class was 67,78. Based on the compilation, a t-test showed that the t-count was 6.114 with a significance of 0.000. It means the t-value was significant (0.000 < 0.005). In conclusion, it can be stated that the Taboo game was effective in improving students’ vocabulary mastery at seventh-grade MTs. Ma’arif Balong. The appropriate media are able to attract the students’ interest in learning for instance Taboo games.